1978
DOI: 10.2135/cropsci1978.0011183x001800030012x
|View full text |Cite
|
Sign up to set email alerts
|

Irradiance Response of Tall Fescue Genotypes with Contrasting Levels of Photosynthesis and Yield1

Abstract: The purpose of this study was to determine if genotype by irradiance interactions or genetic variation in diurnal trends of CO2 exchange rate (CER) influenced the CER‐yield relationship in tall rescue (Festuca arundinacea Schreb.). Genotypes were selected in the field for high CER‐high yield, high CER‐lowyield, low CER‐high yield, and low CER‐Iow yield. Responses of CER to photosynthetic photon flux density (PPFD) of these genotypes were determined using both growth chamber‐ and field‐grown material. The shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
4
9
0
Order By: Relevance
“…In the growth chamber, leaf growth rates of high-yielding genotypes were 54y0 greater than low-yielding genotypes. T h e highest yielding genotype in these studies, L-H, (Wilhelm and Nelson, 1978) was consistently high in leaf growth rate, which supports the conclusion of Horst (1973) that leaf growth rate was closely associated with forage yield.…”
Section: Long-term Leaf Growthsupporting
confidence: 85%
See 3 more Smart Citations
“…In the growth chamber, leaf growth rates of high-yielding genotypes were 54y0 greater than low-yielding genotypes. T h e highest yielding genotype in these studies, L-H, (Wilhelm and Nelson, 1978) was consistently high in leaf growth rate, which supports the conclusion of Horst (1973) that leaf growth rate was closely associated with forage yield.…”
Section: Long-term Leaf Growthsupporting
confidence: 85%
“…They suggested that factors such as genotypic variation in leaf aging and canopy architecture may have a dominant influence on dry matter production of each genotype, regardless of CER. Wilhelm and Nelson (1978) selected genotypes of tall fescue with combina- 'Contribution from the Missouri Agric. Exp.…”
Section: Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Genotypes used in this study were originally selected for early flowering. Yield and CER of these genotypes were originally determined in field studies during 1972 and 1973 and are described by Wilhelm and Nelson (1978a). In general, the high category genotypes had about 30% greater CER and 32y0 greater yield than did the low category genotypes.…”
Section: Methodsmentioning
confidence: 99%